Analysis of Students' Mathematical Reasoning Abilities on Matrix Material at Senior High School - Umar, Ishak; Badu, Syamsu Qamar; Kobandaha, Putri Ekawaty (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The objective of this study is to describe the mathematical reasoning abilities of eleventh-grade students at public senior high school 1 Limboto, focusing on matrix material. This type of research employs quantitative methods and descriptive approaches. The subjects of the research consisted of 30 students from grade XI (IPA 1). Data collection was conducted through tests designed to measure various indicators of mathematical reasoning abilities. The results indicated that, overall, students' mathematical reasoning abilities fell into the moderate category, with a percentage of 69.33%. Further analysis based on the reasoning indicators revealed varied results: the ability to write mathematical statements was categorized as moderate (82.22%); the ability to perform manipulations was categorized as high (86.67%); the ability to find patterns in mathematical phenomena was moderate (74.67%); and the ability to draw conclusions from solutions was categorized as very low (39.26%). These findings highlight the need for greater attention to drawing conclusions in the learning process so that students can enhance their overall mathematical reasoning abilities.